Exploring health stakeholders' perceptions on moving towards comprehensive primary health care to address childhood malnutrition in Iran: a qualitative study - Saikia Udoy; Coveney John; Javanparast Sara (BMC, 2009)
Abstract Background Due to the multifaceted aspect of child malnutrition, a comprehensive approach, taking social factors into account, has been frequently recommended in health literature. The Alma-Ata declaration explicitly outlined comprehensive primary health care as an approach that addresses the social, economic and political causes of poor health and nutrition. Iran as a signatory country to the Alma Ata Declaration has established primary health care since 1979 with significant progress on many health indicators during the last three decades. However, the primary health care system is still challenged to reduce inequity in conditions such as child malnutrition which trace back to social factors. This study aimed to explore the perceptions of the Iranian health stakeholders with respect to the Iranian primary health care performance and actions to move towards a comprehensive approach in addressing childhood malnutrition. Health stakeholders are defined as those who affect or can be affected by health system, for example health policy-makers, health providers or health service recipients. Methods Stakeholder analysis approach was undertaken using a qualitative research method. Different levels of stakeholders, including health policy-makers, health providers and community members were interviewed as either individuals or focus groups. Qualitative content analysis was used to interpret and compare/contrast the viewpoints of the study participants. Results The results demonstrated that fundamental differences exist in the perceptions of different health stakeholders in the understanding of comprehensive notion and action. Health policy-makers mainly believed in the need for a secure health management environment and the necessity for a whole of the government approach to enhance collaborative action. Community health workers, on the other hand, indicated that staff motivation, advocacy and involvement are the main challenges need to be addressed. Turning to community stakeholders, greater emphasis has been placed on community capabilities, informal link with other social sectors based on trust and local initiatives. Conclusion This research provided a picture of the differences in the perceptions and values of different stakeholders with respect to primary health care concepts. The study suggests that a top-down approach, which still exists among health policy-makers, is a key obstacle that delays, and possibly worse, undermines the implementation of the comprehensive strategy codified by the Alma-Ata Declaration. A need to revitalise primary health care to use its full potential and to combine top-down and bottom-up approaches by narrowing the gap between perceptions of policy makers and those who provide and receive health-related services is crucial.